PERAN LSM DALAM PENGUNGKAPAN KASUS KORUPSI JALAN LINGKAR KOTA SALATIGA - Pramadhika Ferdhian Kusuma Wardhana; Purwoko .; Rina Martini (Journal of Politic and Government Studies, 2014)
Corruption has been exsited in Indonesia since long time ago and become a hereditary tradition from Orde Lama, Orde Baru, up to this present Reformation Era. Corruption in this country has reached epidemic level and threatens this nation, which is why cleaning up the enroot culture of corruption is needed, starting from the morality, behavior, and bureaucracy that might influence us to do something corrupt. The reasons for corruption are vary. Corruption is often attributed to the low salary, the wish to gain a lot of money in just a short time, and the influence of others, or even ourselves. Many efforts have been made by previous government and people to put a stop to it.Indonesia's Corruption Eradicaton Commision (Indonesian: Komisi Pemberantasan Korupsi, abbreviated KPK) is a government agency established to fight corruption. There is also a lot of Non-governmental Organizations (abbreviated NGO) that operate independently of government which has been recognized by Indonesian citizen and government itself. The spirit of "Good Governance, dare to be honest is cool" and stiff penalties that await are hoped can reduce corruption to the barest minimum. Corruption is not only performed in national scope, but also in regional scope. There is a space within our regional autonomy which gives every region its own freedom to manage, build and develop its own region.Salatiga has been spotted because one of local important figure that conducted corruption. The project of Salatiga Ring Road has been corrupted for campaign fund of one of the candidates of the mayor of Salatiga, and using that money he is now sitting as the mayor of Salatiga. Non-governmental Organization and local government took part in solving the corruption, with the help of Financial Investigation Bureau of Indonesia (Indonesia: Badan Pemeriksa Keuangan, abbreviated BPK) and the people of Salatiga.